A Study of the Used Vocabulary Learning Strategies by Teachers for Elementary Stages in Jordanian English language Curriculum in Public Schools - Aldmour, Magda Abdullah Yasin (Journal of Educational and Psychological Sciences, 2019)
This study aimed to presenting vocabulary using several strategies by Jordanian English teachers in public schools, the effectiveness of using several strategies in teaching target words supported the leaning and teaching process regardless of the presented vocabulary, while this study analyses what are the needed meaningful vocabulary learning strategies for elementary stages. Also this study presents the vocabulary without repetition of frequent words occurrences. Moreover, the explaining for what are the used strategies for teaching vocabulary simplify and enhance the teaching process and learning too. The study is based on qualitative research, in which 5 school students were investigated. The participants were asked to take a vocabulary tests. The data of the research indicates that there are significant differences between using meaningful strategies in teaching vocabulary and traditional ones. Effective using several strategies simplify the learning process and make students have a positive attitude towards the second language.